Bacteremia in critically ill immunocompromised patients with acute hypoxic respiratory failure: A post-hoc analysis of a prospective multicenter multinational cohort - Van de Louw, Andry; Rello, Jordi; Martin-Loeches, Ignacio; Mokart, Djamel; Metaxa, Victoria; Benoit, Dominique; Barratt-Due, Andreas; Soares, Marcio; Pickkers, Peter; Antonelli, Massimo; Demoule, Alexandre; Schellongowski, Peter; et al. (Journal of critical care, 2021)
PURPOSE: The characteristics and impact of bacteremia have not been widely investigated in immunocompromised patients with acute respiratory failure (ARF). METHODS: We performed a secondary analysis of a prospective cohort of immunocompromised patients with ARF (EFRAIM study). After exclusion of blood cultures positive for coagulase negative Staphylococci, we compared patients with (n = 236) and without (n = 1127) bacteremia. RESULTS: The incidence of bacteremia was 17%. Bacterial pneumonia and extra-pulmonary ARDS were the main causes of ARF in bacteremic patients. Bacteremia involved gram negative rods (48%), gram positive cocci (40%) or were polymicrobial (10%). Bacteremic patients had more hematological malignancy, higher SOFA scores and increased organ support within 7 days. Bacteremia was associated with higher crude ICU mortality (40% versus 32%, p = 0.02), but neither hospital (49% versus 44%, p = 0.17) nor 90-day mortality (60% versus 56%, p = 0.25) were different from non-bacteremic patients. After propensity score matching based on baseline characteristics, the difference in ICU mortality lost statistical significance (p = 0.06), including in a sensitivity analysis restricted to patients with pneumonia. CONCLUSIONS: We analyzed a large population of immunocompromised patients with ARF and an incidence of bacteremia of 17%. We could not demonstrate an impact of bacteremia on mortality after adjusting for baseline characteristics.
Keywords: kritický stav; Prospective Studies; Respiratory Distress Syndrome; imunokompromitovaný pacient; Critical Illness; Immunocompromised Host; respirační insuficience; bakteriemie; lidé; jednotky intenzivní péče; syndrom dechové tísně; Bacteremia; Humans; Respiratory Insufficiency; prospektivní studie; Intensive Care Units